An Exploration of Islamic Educational Values in Malay Cultural Traditions for Character Development among Students in Muara Bungo - Anna apriyeni; Baili; ulfa Adilla; Mabruri; Andryadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
This study aims to explore and analyze the Islamic educational values embedded in the traditions of the Malay community in Muara Bungo, Bungo Regency, Jambi Province, and their relevance to strengthening students’ character in formal educational institutions. Employing a descriptive qualitative approach with an ethnographic design, data were collected through participant observation, in-depth interviews with traditional leaders, Islamic education teachers, parents, and students, as well as document analysis of local curricula, cultural archives, and regional regulations. The findings identify four core values that remain actively practiced within the community: (1) the principle of adat bersendi syarak, syarak bersendi Kitabullah as the philosophical foundation of religious character formation; (2) traditions such as kenduri, maulidan, and batobo as mediums for fostering social ethics, empathy, and collective responsibility; (3) the culture of respecting teachers and parents, which reinforces discipline, learning ethos, and moral obedience; and (4) the integration of Islamic and customary values into school learning practices through local content subjects and extracurricular activities. These findings are discussed within the framework of local wisdom-based character education and contemporary Islamic pedagogy. The study concludes that the Malay traditions of Muara Bungo are not merely cultural heritage but also valuable educational resources for strengthening students’ religious, social, and national character. It is recommended that these values be systematically integrated into Islamic Religious Education (PAI) modules, teacher professional development programs, and school policies grounded in measurable local wisdom-based approaches.